1998
DOI: 10.1074/jbc.273.4.1859
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GRP1-catalyzed ADP Ribosylation Factor Guanine Nucleotide Exchange by Phosphatidylinositol 3,4,5-Trisphosphate

Abstract: Here we show that dioctanoyl PtdIns(3,4,5)P 3 binds the PH domain of GRP1 with a K d ‫؍‬ 0.5 M, an affinity 2 orders of magnitude greater than dioctanoyl-PtdIns(4,5)P 2 . Further, the Sec7 domain of GRP1 is found to catalyze guanine nucleotide exchange of ARF1 and -5 but not ARF6. Importantly, PtdIns(3,4,5)P 3 , but not PtdIns(4,5)P 2 , markedly enhances the ARF exchange activity of GRP1 in a reaction mixture containing dimyristoylphosphatidylcholine micelles, 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 28 publications
11
110
1
Order By: Relevance
“…In addition, Arf proteins are affected by phosphoinositides. Both Arf exchange factors (10,(53)(54)(55)(56) and GAPs (27,28,42) contain PH domains and are activated by phosphoinositides. Thus, PtdInsP 2 could function as a Effect of ASAP1 overexpression on cell spreading rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Arf proteins are affected by phosphoinositides. Both Arf exchange factors (10,(53)(54)(55)(56) and GAPs (27,28,42) contain PH domains and are activated by phosphoinositides. Thus, PtdInsP 2 could function as a Effect of ASAP1 overexpression on cell spreading rate.…”
Section: Discussionmentioning
confidence: 99%
“…Grp1 exchange activity toward myristoylated Arf1 can be enhanced in vitro by PtdIns-3,4,5-P 3 -containing micelles, suggesting that PtdIns-3,4,5-P 3 regulates Grp1 by recruiting it to membranes where Arf is localized (73).…”
Section: Minireview: Role Of Pi 3-kinase Lipid Products 8348mentioning
confidence: 99%
“…Analysis of its amino acid sequence revealed a PH domain and a Sec7 homology domain. The Grp1 PH domain is very selective for PtdIns-3,4,5-P 3 compared with other phosphoinositides (73). The Sec7 homology domain of Grp1 was shown to function as a guanine nucleotide exchange factor for the small G proteins Arf1 and Arf5.…”
Section: Pi-345-pmentioning
confidence: 99%
“…A group of proteins has been identified that possess a certain type of pleckstrin homology (PH) domain that interacts specifically with PtdIns-(3,4,5)P $ and, often, its immediate breakdown product, PtdIns(3,4)P # , also thought to be a signalling lipid (reviewed in [2]). These include the serine\threonine-specific protein kinases, protein kinase B (PKB) and 3-phosphoinositide-dependent protein kinase-1 (PDK1) [3], Bruton's tyrosine kinase (BTK) [4], the adaptor proteins DAPP1 (dual adaptor for phosphotyrosine and 3-phosphoinositides) [5,6] and Gab1 [7], as well as the ADPribosylation factor (ARF) GTPase-activating protein (GAP) centaurin-α [8] and the ARF guanine-nucleotide-exchange factor, Grp1 [9,10].…”
Section: Introductionmentioning
confidence: 99%